2019
DOI: 10.1038/s41598-019-47640-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of motor preparation on the processing of action-relevant visual features

Abstract: Action preparation can facilitate performance in tasks of visual perception, for instance by speeding up responses to action-relevant stimulus features. However, it is unknown whether this facilitation reflects an influence on early perceptual processing, or instead post-perceptual processes. In three experiments, a combination of psychophysics and electroencephalography was used to investigate whether visual features are influenced by action preparation at the perceptual level. Participants were cued to prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…The independence assumption regarding the selection and the execution of a response allows to replace the response selection process with the period (often called "foreperiod", FP) between the presentation of a preliminary warning signal or a response direction cue and an imperative go signal, prompting the selected response execution [5]. A long FP leads to the emergence of a complex effect including a decrease in the response latency and an increase in its accuracy [6][7][8][9] as well as a decrease in the sensory thresholds of the response-relevant features of the imperative signal [7,10]. Korolczuk et al [11] investigated FP-bound mechanisms of response preparation and found an increase in general response inhibition and selected response facilitation.…”
Section: Introductionmentioning
confidence: 99%
“…The independence assumption regarding the selection and the execution of a response allows to replace the response selection process with the period (often called "foreperiod", FP) between the presentation of a preliminary warning signal or a response direction cue and an imperative go signal, prompting the selected response execution [5]. A long FP leads to the emergence of a complex effect including a decrease in the response latency and an increase in its accuracy [6][7][8][9] as well as a decrease in the sensory thresholds of the response-relevant features of the imperative signal [7,10]. Korolczuk et al [11] investigated FP-bound mechanisms of response preparation and found an increase in general response inhibition and selected response facilitation.…”
Section: Introductionmentioning
confidence: 99%